The Postcolonial Body in Queer Space and Time. (Cambridge Scholars Pub., 2006)
The Postcolonial Body in Queer Space and Time examines the ways in which the notion of the postcolonial correlates to Judith Halberstamâ's idea of queer space and time, the non-normative path of Western lifestyles and hegemonies. Emphasizing authors fro.